Pengaruh Store Image Perception, Dan Store Brand Price Image Terhadap Store Brand Purchase Intention Dengan Perceived Risk Sebagai Variabel Mediasi - Didy Surjana (Universitas Tarumanagara, 2019)
The store brand is one of strategy that retailers used for competing in the market which is getting tighter every single day. Based on previous research, there were several factor that influence purchase intention.this study aims to determine the effect of, strore image, perceived risk, and price image on purchase intention at modern market in Jakarta. The researh method used in this study is PLS-SEM, and the data collected by structured quistionaires. Sample that used in this study is 204 respondents. And as the result, the direct effect of store image is the only variabel that wasn’t had a significant influence on purchase intention.